EVALUASI PENGGUNAAN OBAT PENYAKIT INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA ANAK DI INSTALASI RAWAT INAP RSIA CITRA INSANI - Humaira Fadhilah; Gina Aulia; Erika Suci Delia (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
Acute Respiratory Infection (ARI) is a disease that many people suffer from, and is still a major health problem in Indonesia. ARI is a disease caused by various kinds of microorganisms and can cause infection. Deaths caused by infection are 2-6 times higher in developing countries. The purpose of this study was to determine the evaluation of the use of drugs for acute respiratory infections (ARI) in children at the Inpatient Installation of RSIA Citra Insani . This study used a descriptive design with retrospective data collection. The data used in this study were ARI medical record sheets in pediatric patients at the RSIA Citra Insani Inpatient Installation. This study used a total sampling technique and obtained 80 patients who met the inclusion criteria. Based on the results of the study, it was known that the characteristics of pediatric ARI patients based on age <5 years were 50 patients (62.50%), and based on gender, 45 patients (56.52%) were female. The use of ARI drugs based on the most common class was antipyretic as many as 78 (31.45%), and based on the type the most was paracetamol as many as 78 (31.45%). Evaluation of drug use on each criterion, namely the right indication (100%), the right drug (100%), the right dose (93.75%), and the right patient (100%).